2021
DOI: 10.1038/s41467-021-24175-9
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous formation of trihydrogen cations from water on nanoparticles

Abstract: Regarded as the most important ion in interstellar chemistry, the trihydrogen cation, $${{\rm{H}}}_{{{3}}}^{+}$$ H 3 + , plays a vital role in the formation of water and many complex organic molecules believed to be responsible for life in our universe. Apart from trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…In particular, the method facilitates the imaging of the enhanced near-fields around dielectric nanoparticles [ 12 ], while also providing information about their morphology [ 13 ]. Recently, reaction nanoscopy unveiled the laser-induced formation of trihydrogen cations on water-covered silica nanoparticles, thereby extending its application to surface photochemistry [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the method facilitates the imaging of the enhanced near-fields around dielectric nanoparticles [ 12 ], while also providing information about their morphology [ 13 ]. Recently, reaction nanoscopy unveiled the laser-induced formation of trihydrogen cations on water-covered silica nanoparticles, thereby extending its application to surface photochemistry [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have revealed that the measured ion momentum distribution closely follows the distribution of the optical near-field on the nanoparticle surface [ 12 , 13 ]. So far, reaction nanoscopy has been demonstrated for linearly polarized fields at wavelengths of 720 nm [ 12 ] and 1030 nm [ 13 , 14 ]. In addition to the near-field, reaction nanoscopy also allows a mapping of chemical reaction yields on a nanoparticle surface with nanometer resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from the deprotonation process induced in nanosystems, detection of H 3 + ions forming in the strong field interaction of nanospheres via reaction involving two water molecules attached to the nanosurface has been reported (shown in Figure 11 ). 102 In this study, nanoparticles provide a unique environment including nanoscale near-field enhancement, electron trapping, local charge interactions, etc. Complex molecular reactions via four different pathways were expected for the formation of trihydrogen cations, where hydrogen migration is necessary.…”
Section: Ultrafast Molecular Dynamics In Nanosystemsmentioning
confidence: 99%
“… (a and b) Momentum distribution and energy spectra of H 3 + from 300 nm silica nanoparticles. Used with permission from ref ( 102 ). Copyright 2021 Alghabra et al (c) The time of flight (TOF) spectra for ion emission from D 2 O in gas phase and on nanoparticles.…”
Section: Ultrafast Molecular Dynamics In Nanosystemsmentioning
confidence: 99%
“… 5 These properties allow us to precisely modify materials and to investigate ultrafast mechanisms during phase transitions or biochemical and chemical reactions. 1 , 6 9 …”
Section: Introductionmentioning
confidence: 99%